Serial Multiplex PCR May Help Differentiate Causal Pathogens from Colonizing Organisms in Children with Acute Diarrhea in Guatemala. (4th October 2017) - Kamidani, Satoshi; Melgar, Mario; Calvimontes, Diva M; Asturias, Edwin J; Contreras-Roldan, Ingrid; Dominguez, Samuel; Robinson, Christine C; Lamb, Molly; Berman, Stephen; Gaensbauer, James
Abstract: Background: Determination of the cause of childhood diarrhea in low- and middle-income countries is complicated by the presence of multiple potential pathogens in stool at the time of illness. Serial multiplex PCR may offer a method to characterize pathogens more likely to clear over time (suggesting a higher likelihood of causality) vs. those that are more typically persistent (suggesting higher likelihood of nonpathogenic colonization). Such determination may have both clinical and epidemiologic utility. Methods: Children 6–35 months old with acute non-bloody diarrhea (duration <72 hours) were enrolled in a clinical trial between 3/2015 and 1/2016 in three sites (one rural, two urban) in Guatemala. Stool collected at enrollment and 31 days later were analyzed by multiplex PCR (BioFire, USA) that allows simultaneous identification of 22 viral, parasitic and bacterial diarrheal pathogens. Rates of prevalence (positive day 1), persistence (positive both day 1 and 31), and acquisition (negative day 1 and positive day 31) of each pathogen were evaluated. Results: We analyzed 298 subjects with a median age of 17 (range 6–35) months, 54% male and 57% residence in rural areas with poor sanitation. Persistence rates by pathogen are shown in Figure 1. 56% of pathogens on day 1 were persistently positive. Viruses tended to clear from stools over the 31-day period, while parasites and E. coli other than O157:H7 and Shiga toxin-producing E. coli tended to be persistent. New acquisition of at least one pathogen occurred in 80% of children (mean new pathogens 1.7/subject, range 0–7). Day 1 prevalence rates of each pathogen were strongly correlated with acquisition rates in other subjects ( R 2  = 0.818, P  < 0.001), suggesting that these pathogens are efficiently transmitted throughout the community (Figure 2). Similar correlations were observed in both rural and urban populations. Conclusion: Serial multiplex PCR suggests viruses and select bacteria (e.g., E. coli O157:H7) may be more likely causes of acute diarrhea than parasites or certain bacteria (especially less virulent E. coli pathotypes) in Guatemalan children. In addition, pathogens identified by multiplex PCR with high frequency at one time point may enable prediction of future pathogen acquisition in communities. Disclosures: All authors: No reported disclosures.